A new way to produce key streams based on chaotic sequences. (4th July 2018) - Zhou, Xianlin; Ye, Jun
Abstract: In order to enable encryption algorithm to be higher security and better computational efficiency, a new way to produce key stream based on Logistic mapping is proposed. As a result, the key produced by the algorithm has very large key space, and with high secure level.